English Teaching Evaluation in Higher Vocational Education for the Cruise and Art Design Professional Cluster Based on the OBE Concept - Hu, Xiaoli (Journal of Research in Vocational Education, 2025)
This paper centers on the OBE (Outcome-Based Education) concept and explores its application background, implementation plan design, execution, and supportive measures within the context of English teaching evaluation for the Cruise and Art Design professional cluster in higher vocational education. Firstly, the connotation and development of the OBE concept are reviewed, clarifying its applicability in higher vocational English teaching evaluation. Subsequently, the current state of English teaching for this specific professional cluster is analyzed, identifying existing problems. Building upon this analysis, an implementation plan for teaching evaluation based on the OBE concept is designed, encompassing the setting of evaluation objectives and principles, and the construction of an evaluation indicator system. Following this, the implementation process and supportive measures for the plan are elaborated to ensure the effectiveness of the teaching evaluation. Finally, the paper concludes by summarizing the findings and suggesting directions for further research. The research results of this study hold significant theoretical and practical importance for enhancing the quality of English teaching evaluation and promoting the in-depth development of teaching reform within the Cruise and Art Design professional cluster in higher vocational institutions.